2002
DOI: 10.1128/iai.70.2.620-630.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-Binding Proteins of Staphylococcus aureus Are Involved in Adherence to Human Airway Epithelium

Abstract: This study was designed to investigate the molecular mechanisms of Staphylococcus aureus adherence to human airway epithelium. Using a humanized bronchial xenograft model in the nude mouse and primary cultures of human airway epithelial cells (HAEC), we showed that S. aureus adhered mainly to undifferentiated HAEC whereas weak adherence (11- to 20-fold lower) to differentiated HAEC was observed (P < 0.01). A fibronectin (FN)-binding protein (FnBP)-deficient strain of S. aureus had a fivefold-lower adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 43 publications
2
54
0
1
Order By: Relevance
“…Other commensals, such as H. influenzae, can colonize airway epithelia at the ALI for days in vitro with no evidence of detrimental effects (Starner et al, 2006). Most reports of S. aureus in vitro interactions with epithelia cell lines use brief incubation times (less than 4 h) to examine adherence (Mongodin et al, 2000;Mongodin et al, 2002;Escotte et al, 2006), although interactions at time points of up to 20 h have been reported using low inocula with no damage to the airway cells (Quinn and Cole, 2007). The reason for these short-term experiments could be due to the in vitro toxicity of S. aureus that results from alphatoxin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other commensals, such as H. influenzae, can colonize airway epithelia at the ALI for days in vitro with no evidence of detrimental effects (Starner et al, 2006). Most reports of S. aureus in vitro interactions with epithelia cell lines use brief incubation times (less than 4 h) to examine adherence (Mongodin et al, 2000;Mongodin et al, 2002;Escotte et al, 2006), although interactions at time points of up to 20 h have been reported using low inocula with no damage to the airway cells (Quinn and Cole, 2007). The reason for these short-term experiments could be due to the in vitro toxicity of S. aureus that results from alphatoxin.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, ClfB was again found to be necessary for colonization (Wertheim et al, 2008), supporting in vitro studies and prompting development of ClfB as a vaccine candidate (Schaffer et al, 2006). One drawback of most studies utilizing human cell lines is that S. aureus exposure to airway epithelial cells in vitro is brief, addressing initial attachment rather than long-term colonization (Mongodin et al, 2002;O'Brien et al, 2002;Roche et al, 2003;Corrigan et al, 2009). Aside from the role of specific adhesins or binding proteins, these studies provide little information on the physiological state of the bacterial cells in this host niche.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Variations in binding between strains of S. aureus have been shown to, for example, collagen, 28 and fibronectin. [29][30][31] Further extensive studies are required to investigate and elucidate possible differences in adherence between strains of S. intermedius.…”
Section: Discussionmentioning
confidence: 99%
“…Mongodin et al [5] demonstrated the major role of FnBPs in S. aureus adherence to human airway epithelium, whereas staphylococcal protein A and clumping factor did not play any role in this process. These authors also reported that 97% of 32 clinical strains, isolated from the airway secretions of patients with cystic fibrosis and nosocomial pneumonia, possessed the two fnb genes.…”
Section: Discussionmentioning
confidence: 99%